Human rabies in rio Casca municipality, 2012: case report, six years after the last record in Minas Gerais, Brazil (Revista de Educação Continuada em Medicina Veterinária e Zootecnia do CRMV-SP, 2013)
Rabies is a viral disease that affects the central nervous system (CNS) of mammals and it’s fatal in almost 100% of cases. In 2012, six years after the last record of a human case in Minas Gerais, the transmission has been confirmed through aggression by vampire bat. The objective of this report is to describe the clinical and epidemiological characteristics of this case. On 06/19/2012, the Health Department of Minas Gerais State has been notified by the Regional Health Department of Ponte Nova of a suspected case of human rabies from Rio Casca municipality. He was a 32-year-old male patient, farmer, residing in the rural area. The patient suffered bitten by a bat in his right hand after trying to remove it from the back of a calf in the month of May. At that time the patient did not seek medical care and the event was not notified to health service or the agriculture department. The calf died about 10 days after the incident and no material was sent for laboratory examination. Since 06/11/2012, the patient successively sought care because of a barbed wire cutting on the same hand attacked by the bat, which began to show dormancy. Then he developed lip deviation, fever and vomiting, and clinical progression toward paresthesia, insomnia, agitation, confusion, sore throat and drooling. Tetanus, muscle twisting and tonsillitis were diagnostic hypotheses raised by the municipal health services. The aggression was reported only after assistance at Ponte Nova municipality, and suspected human rabies was notified. On the same day, the patient was transferred to the referral hospital in Belo Horizonte municipality for specialized care. Patient sedation was maintained, with antiviral administration and control of symptomatic complications. The patient developed hypernatremia, ventilator-associated pneumonia and cardiac arrests. There was antemortem laboratory confirmation of rabies infection by Polymerase Chain Reaction (PCR) in cerebrospinal fluid and saliva sample, and genetic sequencing indicated that it was compatible with Desmodus rotundus genetic variant. Despite specific treatment, the patient died on 06/28/2012 due to refractory circulatory shock. Postmortem examination was performed by direct immunofluorescence reaction, with infection confirmation at CNS fragments. During the conduct of the case, epidemiological investigation was proceeded by medical reports and records reviewing, family interviews and active search of exposed. In association, health education, social mobilization and intersectoral work actions were developed. Through the described information it is evident the importance of health systems being able to properly suspect, notify, and investigate, added to need to maintain surveillance and control activities of rabies in Minas Gerais state.